Child and youth mental health and wellbeing before and after returning to in-person learning in secondary schools in the context of COVID-19 - Qian, Lei; McWeeny, Robert; Shinkaruk, Cheryl; Baxter, Andrew; Cao, Bo; Greenshaw, Andy; Silverstone, Peter; Pazderka, Hannah; Wei, Yifeng (Frontiers in Public Health, 2023)
Background: Early in the COVID-19 pandemic, many children and youth experienced changes in school routines and mental health. As children reintegrate with in-person classroom learning after COVID-19, health and education institutions should remain mindful of students’ mental health. There is a paucity of data on changes in students’ mental health before, during and after their return to in-person classroom learning in this context. Methods: We collected and analyzed data on self-reported well-being, general mental health, perceived stress, and help-seeking attitudes (including sources of help) from grade 7–12 students in a Catholic school division in Canada (n=258 at baseline; and n=132 at follow-up). Outcomes were compared according to demographic differences such as gender, grade level, experience accessing mental health services, and presence of support staff in schools between baseline and follow-up. Effects of time points and each demographic variable on each outcome and on the prediction of students’ well-being and general mental health were also analyzed. Results: No significant differences were apparent for outcomes between baseline and follow-up. However, specific subgroups: such as junior high students, male students, students who had not accessed mental health services, and students who had access to support-staff had better outcomes than their counterparts. Within-group analyses indicated that From baseline to follow-up, male students reported mental health decline (Mean=11.79, SD=6.14; Mean=16.29, SD=7.47, F(1, 333)=8.36, p<.01); students who had not accessed mental health services demonstrated greater stress (Mean=20.89, SD=4.09; Mean=22.28, SD=2.24, F(1, 352)=6.20, p<.05); students who did not specify a binary gender reported improved general mental health (Mean=19.87, SD=5.89; Mean=13.00, SD=7.40, F(1, 333)=8.70, p<.01), and students who did not have access to support-staff improved help-seeking attitudes (Mean=22.32, SD=4.62; Mean=24.76, SD=4.81; F(1, 346)=5.80, p<.05). At each time point, students indicated parents, guardians, and close friends as their most-preferred help-seeking sources. High stress predicted lower well-being at baseline, but higher well-being at follow-up. Conclusion: Students presented relatively stable mental health. Specific demographic Subgroups with decreased mental health by time may benefit from extra mental health support through building capacity among teachers and health care professionals to support students following public health emergencies that affect access to in-person experiences.